2019
DOI: 10.1002/bjs.11096
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre propensity score-matched study of laparoscopic versus open repeat liver resection for colorectal liver metastases

Abstract: Background: Repeat liver resection is often the best treatment option for patients with recurrent colorectal liver metastases (CRLM). Repeat resections can be complex, however, owing to adhesions and altered liver anatomy. It remains uncertain whether the advantages of a laparoscopic approach are upheld in this setting. The aim of this retrospective, propensity score-matched study was to compare the short-term outcome of laparoscopic (LRLR) and open (ORLR) repeat liver resection.Methods: A multicentre retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 43 publications
4
39
0
Order By: Relevance
“…This led to a distortion of our results. Other studies showed a shorter LOPS with a mean hospitalization stay of 3–5 days 7 , 33 , 35 . First, Rebibo et al presented a pilot study with minor laparoscopic liver resections as a day-case surgery without overnight hospitalization 36 .…”
Section: Discussionmentioning
confidence: 86%
“…This led to a distortion of our results. Other studies showed a shorter LOPS with a mean hospitalization stay of 3–5 days 7 , 33 , 35 . First, Rebibo et al presented a pilot study with minor laparoscopic liver resections as a day-case surgery without overnight hospitalization 36 .…”
Section: Discussionmentioning
confidence: 86%
“…Neither the postoperative complication rate nor the hospital stay was affected by abdominal adhesions in those patients. The above also applies to repeated liver resections, as recently shown for both CRLM and HCC [ 46 , 47 ]. If repeated liver resection is considered possible laparoscopically, patients have common advantages over the open technique, e.g., less blood loss, a lower complication rate, and reduced hospital stay.…”
Section: Limitationsmentioning
confidence: 88%
“…Currently, there is no randomized-control trial for open and laparoscopic repeat resection and only four propensity-score matching studies [ Table 1] [31][32][33] . Besides our study, the studies include patients with other diseases than HCC with few data for long-term results.…”
Section: The Propensity Score Matching Study For Hcc Patientsmentioning
confidence: 99%